Signal intensity loss on t2-weighted gradient-recalled echo magnetic resonance images in the basal ganglia in a patient with chronic hepatic encephalopathy - Permphan Dharmasaroja (2018)
Background: Bilaterally symmetrical hyperintensity on T1-weighted magnetic resonance images (MRIs) without abnormalities on T2-weighted images in the basal ganglia is described in patients with chronic liver disease. Manganese, which escapes hepatic clearance because of a portosystemic shunt or liver dysfunction, is thought to be involved in alterations of signal intensity on MRIs, and exerts neurotoxicity, which results in neuropsychiatric disturbances including extrapyramidal symptoms. Rationales and case: Currently, reports evaluating interpretations of hyperintensity on T1- and normal intensity on T2-weighted images still provide conflicting results. T2-weighted gradient-recalled echo (GRE) MR imaging is dependent on magnetic susceptibility effect and is highly sensitive to static magnetic field inhomogeneity. Field distortions caused by material with high magnetic susceptibility induce signal intensity loss, resulting in typical signal intensity voids. This article describes asymmetric signal intensity loss on T2-weighted GRE MRIs in the globus pallidus in a patient with chronic hepatitis C infection presenting with a gradual onset of lethargy, dysarthria, and gait instability; whereas T1-weighted MRIs showed symmetrical hyperintensity in this region and the midbrain and T2-weighted images showed normal signal intensity. Conclusion: T2-weighted GRE MR imaging should be included in brain MR imaging studies of patients with chronic liver disease presenting with extrapyramidal symptoms for better localization of the lesions. © 2010 by Lippincott Williams & Wilkins.